Standardization of techniques for seed germination in Reetha (Sapindus mukorossh - Thakur, Sanjeev; Sharma, Kamal; Gupta, Atul; Guleria, Vipan (Indian Journal of Agroforestry, 2020)
The present study was conducted from April. 2010 to July 2010 to ascertain the effect of different pre treatments on seed germination in Reetha (Sapindus mukorossi). Scarification of seed with concentrated sulphuric acid for 30 minutes before sowing resulted in 83.40 percent germination as compared to 26.40 percent in control. Germination energy (70%) was also found maximum with the same seed treatment.